Canteen Food Ordering and Management Application - Zul, Nur Syazwani; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2022)
School canteens play an important role in providing food to students and the rest of the school community and normally, students have to make long queues for placing the order but in fact, with the state of the country facing this Covid-19 pandemic, the queuing method to buy food at school is no longer appropriate. The purpose of developing this application is to help parents to place orders on behalf of their children in order to avoid overcrowding at the canteen. Agile-based methodology is used as the methodology to develop this application. Several technologies are used such as mobile technology (android platform), Android Studio with Flutter and Dart Extensions and object-oriented programming. This application is expected to help parents and canteen workers find an automated way to order food easily while at the same time curbing the transmission of covid-19 among students when buying food.